Climate Donations Inspired by Evidence-Based Fundraising - Ryba, Ren; Dry, Matthew J.; Connell, Sean D. (Frontiers in Psychology, 2022)
Everyone has an opportunity to contribute to climate solutions. To help people engage with this opportunity, it is critical to understand how climate organizations and fundraisers can best communicate with people and win their financial support. In particular, fundraisers often rely on practical skills and anecdotal beliefs at the expense of scientific knowledge. Fundraisers could be motivated to achieve a substantial boost in funding for climate solutions, if there is evidence of the financial gains that science-based fundraising makes available. In this Perspective, we provide a preliminary foray into such evidence. We bring together findings from philanthropic research and climate psychology to identify what factors can help captivate donors. Then, through an experimental study of a charitable appeal for a climate charity, we show how putting these factors into practice may contribute towards an increase in donated money. This provides optimism that evidence-based fundraising can inspire donors to contribute much-needed resources towards climate solutions.